ELECTRONEUROMYOGRAPHIC STUDY FOR CARPAL TUNNEL STENOSIS - Takhirov Zh. M.; Asilova S. U.; Nurimov G. K. (Web of Journals Publishing, 2024)
Electroneuromyographic ( ENMG ) study _ allows you to determine changes in the bioelectrical activity of the hand muscles depending on the degree of carpal tunnel stenosis, and is also an objective criterion for assessing the results of treatment of orthopedic and trauma patients . We observed 45 patients with carpal tunnel stenosis of varying degrees . In this case, stenosis I degree was observed in 8 patients, II degree in 15 patients with conservative treatment and III degree in 22 patients with surgical treatment according to what we developed. EMG studies were carried out in the immediate (before and after treatment) and long-term (after 6 months) periods. In a comparative study of EMG parameters between groups, a significant increase in the amplitude and frequency of oscillations was observed in all leads in patients receiving surgical treatment compared to the group receiving conservative treatment. (р˂0.01). Analysis of the data obtained showed that after treatment, patients with surgical treatment showed an improvement in the functional state of the hand muscles.
Keywords: Electroneuromyography, carpal tunnel stenosis, bioelectrical activity of hand muscles, degree of disease.